The feasibility of using the Körperkoordinationstest fur Kinder (KTK) in a U.S. elementary physical education setting to assess gross motor skills specific to postural balance - Campbell-Pierre, Daryl; Rhea, Deborah J. (Frontiers in Sports and Active Living, 2023)
Introduction For the past ten years, falls have been the leading cause of nonfatal injuries for all age groups less than 15 years old. A significant rise in childhood sedentary behavior in schools and limited opportunities to be outside has led to motor coordination deficits which have contributed to fall injuries. Method A German assessment tool, the Körperkoordinationstest fur Kinder (KTK), which has been used for decades in Western European countries, allows researchers and physical education teachers to evaluate typical and atypical children's motor coordination competencies related to dynamic postural balance successfully. No research has been published on the use of this assessment tool in the United States. If its use were found to be feasible in this country for identifying motor coordination deficits in typical and atypical children, it would close the gap in determining motor coordination. Therefore, this study sought in Phase 1 to determine the feasibility of using the KTK assessment in U.S. children and Phase 2 sought to determine the adaptability of the scoring protocol from use in other countries to the United States. Results The Phase 1 results revealed the KTK assessment was feasible to administer in U.S. physical education class by addressing three challenges for U.S. schools: 1) KTK implementation, 2) time to assess each skill, and 3) the equipment availability and cost to implement the test in a physical education setting. In Phase 2, the researchers were able to determine the raw scores and motor quotient scores in this population and then were able to show similar scoring trends between U.S. children and Flemish children from a previous study. Conclusion This assessment tool was deemed feasible and adaptable which is the first step to use the KTK in U.S. physical education elementary school settings.